Quotidiana : immagini della vita di ogni giorno nell'arte del XX secolo. - Beccaria, Marcella; Cherubini, Laura; De Cecco, Emanuela; Gianelli, Ida; Gioni, Massimiliano; Miller, Dana; Momin, Shamim; Ross, David; Serota, Nicholas; Swenson, Ingrid; Verzotti, Giorgio; Watkins, Jonathan; et al. (Milano : Edizioni Charta Milano, 2000)
Avant-garde contemporary art is usually considered an intellectual and elitist cultural activity, extraneous to the "banal" reality of everyday existence. This is not really true. The avant-garde often stems directly from the quotidian - from an existential dimension that can be easily generalized - to make a criticism of it or to unveil its hidden or censored side, or to prefigure a utopian change of the quotidian itself. In most cases the contents dealt with by the avant-garde describe a reality which everyone can experience, even though the language used by the artist renders it less easily understandable. In fact the artist imparts an interpretation which transforms the real in a poetic or polemical way, but at the same time offers clues to its reading.
The aim of Quotidiana is to investigate the different ways in which contemporary art has turned to the everyday with a selection of works that document the evolution of the aesthetic languages of the avant-garde from the beginning of the 20th century up to the present.
Airo, Mario ; Artschwager, Richard ; Balla, Giacomo ; Billingham, Richard ; Boccioni, Umberto ; Boltanski, Christian ; Braque, Georges ; Broodthaers, Marcel ; Buren, Daniel ; Calle, Sophie ; Celmins, Vija ; Clark, Larry ; Conner, Bruce ; Cragg, Tony (Anthony) ; Debord, Guy ; diCorcia, Philip-Lorca ; Duchamp, Marcel ; Fischli & Weiss ; Floyer, Ceal ; Fritsch, Katharina ; Gabellone, Giuseppe ; Gilbert & George ; Gober, Robert ; Goldin, Nan ; Gonzalez-Torres, Felix ; Graham, Dan ; Hamilton, Richard ; Hedlund, Maria ; Hopper, Edward ; Jia, Zhu ; Jones, Sarah ; Kabakov, Ilya ; Kawara, On ; Krisanamis, Udomsak ; Lissitzky, El ; Lockhart, Sharon ; Lucas, Sarah ; Moffatt, Tracey ; Morandi, Giorgio ; Nauman, Bruce ; Oldenburg, Claes ; Ono, Yoko ; Pardo, Jorge ; Picasso, Pablo ; Pierson, Jack ; Pistoletto, Michelangelo ; Polke, Sigmar ; Rauschenberg, Robert ; Ray, Charles ; Richter, Gerhard ; Rosler, Martha ; Ruscha, Ed ; Scher, Julia ; Schwitters, Kurt ; Starkey, Hannah ; Streuli, Beat ; Struth, Thomas ; Taylor-Wood, Sam ; Tillmans, Wolfgang ; Toderi, Grazia ; Trockel, Rosemarie ; Vicuña, Cecilia ; Wall, Jeff ; Ward, Nari ; Warhol, Andy ; van Warmerdam, Marijke ; Wearing, Gillian ; Wentworth, Richard ; West, Franz ; Woodrow, Bill ; Zittel, Andrea
biog. & biobliog. per kunstenaar p. 248-279 (Italiaans), p. 280-309 (Engels)
Italiaans & Engels
Quotidiana : the continuity of the everyday in 20th century art, Castello di Rivoli Museo d'Arte Contemporanea, Rivoli (Torino), 5 febbraio - 21 maggio 2000
boek